Blind carrier frequency offset estimation for single carrier and orthogonal frequency division multiplexing signals using least‐order cyclic moments. Issue 6 (1st April 2016) - Yang, Ding; Si, Jiangbo; Li, Zan; Beaulieu, Norman C.; Zhu, Jianfeng; Zhou, Fuhui; Hao, Benjian
Abstract : A definition of least cyclostationary order (LCO) is proposed based on the inner cyclic period of single carrier and orthogonal frequency division multiplexing (OFDM) signals. The LCOs of single carrier and OFDM signals are derived. Since the LCO has a relationship with the carrier frequency offset (CFO), a blind CFO estimation scheme for single carrier and OFDM signals can be proposed. The novel scheme is entirely blind without any priori information and is proved to be the same as cumulants estimation when the LCO is known. However, the new scheme is superior to the estimation based on cumulant when the LCO is unknown. The mean‐square error of M ‐phase shift keying signals approaches the Cramér–Rao bound in additive white Gaussian noise (AWGN) channel. Simulation results are given to verify the effectiveness of the proposed blind estimation scheme in Rician fading channel and in AWGN channel.